Construction and application of universal heavy metal ion electrochemical sensor based on nano-mesoporous silica composites

By encapsulating methylene blue on nanomesoporous silicon materials and combining with ITO electrochemical cells, the sensitivity and universality of heavy metal sensors are solved, and the low concentration of heavy metal ions are achieved. High sensitivity detection, suitable for cadmium rice sample analysis, with the advantages of small volume and low cost.

CN115060770BActive Publication Date: 2025-01-07NINGBO COLLEGE OF HEALTH SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210650012.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-01-07
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

Existing heavy metal sensors have problems such as insufficient sensitivity, lack of small volume analysis systems and poor universality, making it difficult to achieve high sensitivity, accurate and rapid detection of low-concentration heavy metal ions.

Method used

Using a universal heavy metal ion electrochemical sensor based on nanomesoporous silicon composite materials, DNA is used to suit DNA by encapsulating methylene blue (MB) on nanomesoporous silicon materials and combining with negatively charged indium tin oxide (ITO) electrochemical cell. The ligand specifically binds to heavy metal ions to release MB, thereby enabling signal capture and detection.

Benefits of technology

It realizes high sensitivity detection of heavy metal ions, has universality and small volume analysis capabilities, and can accurately detect heavy metal ions of different concentrations, especially cadmium ions. It is suitable for the analysis of cadmium rice samples, with low cost and high detection limits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115060770B_ABST
    Figure CN115060770B_ABST
Patent Text Reader

Abstract

This patent is based on amino-modified nano-mesoporous silicon material encapsulating methylene blue (MB), and uses a homemade negatively charged indium tin oxide (ITO) electrochemical cell to design a universal heavy metal ion electrochemical sensor. The main principle is as follows: using an aptamer that has a good effect on heavy metal ions, when it is present, it triggers the detachment of the aptamer and the nano-mesoporous silicon composite material, so that MB is released. The released MB signal molecules are captured by the negatively charged ITO electrode, so that a large number of signal molecules are gathered on the electrode surface to realize the detection of heavy metal ions. We verified the universality of the heavy metal ion electrochemical sensor designed in this patent for 6 different heavy metal ions, and then tested it for different concentrations of Cd 2+ An analytical study was conducted, and the sensor was applied to the analysis and detection of cadmium rice, providing new ideas for the development of heavy metal ion analysis research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the construction of an electrochemical sensor and its application, in particular to the construction of a universal heavy metal ion electrochemical sensor based on a nano-mesoporous silicon composite material and its application in cadmium rice analysis and detection, and belongs to the technical field of functional nanomaterials and chemical biosensors. Background Art

[0002] Heavy metals generally refer to metals with a specific gravity greater than 5, such as cadmium, mercury, zinc, iron, nickel, cobalt, copper, lead, chromium, etc. With the increasing mining, smelting, processing and commercial manufacturing activities, many harmful heavy metals enter the atmosphere, water, and soil, accumulate, and migrate, causing environmental pollution and endangering the national economic construction; they then enter the human body through the food chain, seriously threatening human health and the harmonious development of society. Therefore, it is very important to conduct highly sensitive, accurate, and rapid on-site detection of low-concentration heavy metal ions. Electrochemical methods have always been the research focus of rapid on-site detection of heavy metal ions, but there are three challenges: the sensitivity of heavy metal sensors needs to be improved; there is an extreme lack of small-volume analysis systems for heavy metal sensors; and the universality of heavy metal sensors needs to be improved.

[0003] Since the discovery of mesoporous silica by researchers at Mobil Oil 20 years ago, the study of ordered mesoporous silica has received more and more attention in recent years. A good mesoporous silica nanocarrier should simultaneously display multiple excellent biological properties, such as ① high visibility, ② good dispersibility, ③ targeting specificity to living tissue cells, ④ loading capacity for high concentrations of cargo, and ⑤ triggering or controlling the release of cargo. These excellent properties have made great progress in the application research of mesoporous silica functional composite nanomaterials in the fields of biomedicine and analytical sensing. Through specific chemical modification, biological modification, and physical modification, it has shown broad application prospects in the fields of controlled drug release, analytical sensing testing, etc.

[0004] The present patent application designs a universal heavy metal ion electrochemical sensor based on amino-modified nano-mesoporous silicon material encapsulating methylene blue (MB) using a homemade negatively charged indium tin oxide (ITO) electrochemical cell. The main principle is as follows: using an aptamer that has a good effect on heavy metal ions, when it is present, it triggers the detachment of the aptamer from the nano-mesoporous silicon composite material, thereby releasing MB. The released MB signal molecules are captured by the negatively charged ITO electrode, thereby a large number of signal molecules are gathered on the electrode surface to realize the detection of heavy metal ions. Using the above-mentioned analytical detection principle, based on the new ITO electrochemical system, we verified the universality of the heavy metal ion electrochemical sensor designed in this patent application for 6 different heavy metal ions, and then selected cadmium ions (Cd 2+ ) was used as the main research object to investigate the different concentrations of Cd 2+The sensor was applied to the analysis and detection of cadmium rice, providing new ideas for the development of heavy metal ion analysis research. This patent application mainly helps to solve the following three problems: the universality of heavy metal sensors; the sensitivity of heavy metal sensors; and the small volume analysis system of heavy metal sensors. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite materials with good specificity, high sensitivity, fast detection speed, accurate and reliable results and low cost and its application.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: construction and application of a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite materials, and the specific steps are as follows:

[0007] (1) Preparation and functionalization of nano-mesoporous silica materials

[0008] 0.5-1.0 g (2-2.7 mmol) of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 200-480 mL of double distilled water, and 1.0-3.5 mL of 1.0-2.0 mol / L sodium hydroxide aqueous solution was added. The mixed solution was placed in an environment of 20-40 ° C and stirred thoroughly. After stirring evenly, the temperature was raised to 60-80 ° C and stirred for an additional 1-2 h. Then, orthosilicate (TEOS) (2.0-5.0 mL 10.0-21.9 mmol) was added dropwise at a rate of 0.5-1.0 mL / min. Stirring was continued until a large amount of white material was seen. After washing with methanol, it was placed in a vacuum drying oven at 50-100 ° C and dried for 6-12 h. The obtained material was named A1. Subsequently, 0.5-1.0 g of A1 was weighed and dispersed in 60-80 mL of toluene, and then 1-5 mL of 3-aminopropyltriethoxysilane was added. After mixing evenly, it was heated in N 2 Reflux overnight under atmosphere, filter, wash alternately with toluene and methanol, and then put the solid into a vacuum drying oven at 15-25°C to dry to obtain solid A2. Weigh 0.5-1.0g of the synthesized solid A2 and add 50-100mL of methanol and 0.5-0.75mL of concentrated hydrochloric acid mixed solution, stir at 37-50°C for 4-6h, filter and vacuum dry at room temperature for 10-12h to obtain solid A3, i.e. nano-mesoporous silicon material. Weigh 5-10mg of A3 powder in 0.5-1.0mL of water, ultrasonically disperse for 1.0-1.5h to obtain a well-dispersed mesoporous silicon solution (concentration: 5-10mg / mL).

[0009] (2) Preparation of nano-mesoporous silica@methylene blue composites

[0010] Take 10-100 μL of 0.1-1 mM methylene blue solution (MB) and add it to the above-mentioned mesoporous silica solution, incubate for 6-12 h under stirring, let it stand for 10-30 min, centrifuge the obtained suspension (1-5 min, 1000-5000 rpm), then wash it with PBS (10 mM, pH 7.0) for 3 times, and finally dissolve the obtained precipitate in 0.5-1.0 mL PBS (10 mM, pH 7.0).

[0011] (3) Preparation of heavy metal ion aptamer-coated nano-mesoporous silica@methylene blue composites

[0012] The nano-mesoporous silica@methylene blue composite material obtained in step (2) is dispersed in 0.5-1.0 mL (10 mM, pH 7.0) solution containing 5-10 μM heavy metal ion aptamer, mixed and placed at 1-4°C for 3-6 hours, the mixed solution is centrifuged (1-5 min, 2000-5000 rpm), and washed with PBS for 1-3 times. Then, the obtained coating material is dispersed in 0.5-1.0 mL PBS (10 mM, pH 7.0).

[0013] (4) Construction of electrochemical substrates for carrying small-volume samples

[0014] Use a diamond knife to separate the purchased ITO whole electrode into a (0.5~1) cm×(0.5~1) cm matrix, and then glue the divided PCR tube sleeve into the ITO matrix with glue, and a simple ITO electrochemical cell is prepared. Subsequently, the ITO surface is cleaned several times with acetone, anhydrous ethanol, and distilled water in turn to remove impurities on the electrode surface, and the electrode is dried with nitrogen. Then, soak the electrode in 0.5~1.0 mol / L HCl for 5~10 minutes, and then wash the electrode surface with distilled water. Immerse the cleaned electrode in (0.5~1):(0.5~1):(2~5)(v / v / v)H 2 O 2 / NH 3 ·H 2 O / H 2 O mixed solution for 0.5 to 1 h to obtain ITO with -OH on the surface. Then, the electrode surface is cleaned with double distilled water and N 2 Dry the electrode.

[0015] (5) Research on universal heavy metal ion electrochemical sensors

[0016] In an environment of 4 to 12° C., 100 to 500 μL of PBS (100 mM, pH 7.0) was placed in the ITO electrochemical cell of step (5), and 1 to 5 μL of different heavy metal ions were added and mixed. Subsequently, 30 to 45 μL of the composite material of step (3) was added, and the signal value of the released MB molecules was continuously collected by square wave voltammetry (SWV).

[0017] Based on the above steps (1)-(5), for 6 different heavy metal ions (such as Cd 2+ , Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + ), by changing the aptamer type in step (3) and keeping other steps unchanged, the detection of 6 different heavy metal ions can be achieved, verifying the universality of the prepared sensor.

[0018] Based on the above steps (1)-(5), select Cd 2+ As the research object, the aptamer used in step (3) is Cd 2+ The aptamer is obtained by changing the Cd 2+ concentration (final concentration: 0, 0.01, 0.03, 0.05, 0.1, 0.5, 1, 3, 5, 8, 10, 20 and 30 μM), and other steps remained unchanged to achieve the effect of Cd 2+ to verify its sensitivity.

[0019] The DNA chains used are as follows:

[0020]

[0021]

[0022] The universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite material is constructed and applied. Square wave voltammetry is used to set the potential range to -0.35 to -0.1 V and the amplitude to 0.025 V. The electrochemical response of the prepared ITO electrochemical system to methylene blue (MB) is used to verify the universality of the method involved in this patent application, and Cd 2+ As a research object, by changing Cd 2+ A series of different concentrations of Cd 2+ The corresponding current size establishes the current response and Cd 2+ The linear relationship between the concentrations of cadmium and rice was used to determine the Cd content in the cadmium rice sample. 2+ Concentration (content).

[0023] Principle of the invention: The present invention is the construction and application of a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite materials. A universal heavy metal ion electrochemical sensor is designed based on amino-modified nano-mesoporous silicon materials that encapsulate MB as an electron transfer medium. DNA aptamers that have a good effect on heavy metal ions are used to trigger the separation of the aptamer and the mesoporous silicon composite material when it is present, so that MB is released. The released MB signal molecules are captured by the negatively charged ITO electrode, thereby a large number of signal molecules are gathered on the electrode surface to realize the detection of heavy metal ions. This patent application utilizes the above-mentioned analytical detection principle and realizes not only the detection of different concentrations of Cd based on the new ITO electrochemical system 2+ The actual cadmium content of rice samples is 2+ The high-sensitivity detection provides a new idea.

[0024] Compared with the prior art, the advantages of the present invention are: the universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite material is constructed and applied. Obviously, within a certain concentration range, Cd 2+ The higher the concentration, the higher the Cd 2+ Aptamers bind to Cd through specific binding 2+ The more the binding, the more MB in the mesoporous silicon is released, and the more obvious the current response is. Similarly, Cd 2+ The lower the concentration, the less aptamers are bound and the weaker the current response. 2+ The concentration showed a linear relationship within a certain range, successfully achieving the Cd 2+ The advantages are:

[0025] (1) Excellent universality. This patent application is for 6 metal ions (Cd 2+ , Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + ) conducted research and, by introducing corresponding aptamers, proved that the heavy metal ion electrochemical biosensor has universal applicability and high application value.

[0026] (2) ITO electrochemical cell with superior performance. An ITO electrochemical cell that can serve as both an electrolyte solution container and a working electrode was constructed using simple ITO glass and common PCR tubes. It is easy to prepare and use, and is suitable for direct analysis of small volume samples, which has great advantages.

[0027] (3) High sensitivity. The present invention is based on Cd 2+The specific binding effect of the aptamer and the sensing effect of the ITO electrode on MB resulted in a linear equation: 2+ The concentration linear correlation equation is y = 0.2874x + 0.7603, R 2 =0.9923, the linear range is 0.01-10 μM, and the detection limit is 0.0026 μM (S / N=3); this indicates that the electrochemical sensor can detect Cd 2+ Achieve high-sensitivity detection.

[0028] (4) High specificity. Using Cd 2+ The electrochemical sensor was fabricated by using aptamers to detect Cd 2+ Detection: Other reference ions such as Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + etc. have no interference to the system, which is helpful to realize the determination of Cd in complex sample rice 2+ Analytical testing.

[0029] (5) The results are accurate. The recovery rate is between 90% and 110%.

[0030] (6) The preparation and detection methods use less reagents and are low in cost. The present invention only requires a small amount of materials and reagents to detect Cd 2+ Highly sensitive detection.

[0031] In summary, the present invention is a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite materials and its application, which has the advantages of high sensitivity, good selectivity, simple operation, fast analysis, and easy operation, and can achieve low concentration Cd 2+ detection, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The experimental diagrams are the responses of the sensor of the present invention to different metal ions;

[0033] Figure 2 The sensor of the present invention is Cd 2+ Experimental diagram of analysis and detection;

[0034] Figure 3 The sensor of the present invention is used to detect different concentrations of Cd 2+ Calibration curve of current response versus concentration;

[0035] Figure 4 The sensor of the present invention is Cd 2+ Specificity experimental diagram.

[0036] Figure 5The sensor of the present invention detects Cd in complex samples 2+ Analysis and detection experiment diagram. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below with reference to the accompanying drawings.

[0038] Example 1: Verification of the universality of the heavy metal ion electrochemical sensor prepared

[0039] (1) Preparation and functionalization of nano-mesoporous silica materials

[0040] 1.0 g (2.7 mmol) of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 480 mL of double distilled water, and 3.5 mL of 2.0 mol / L sodium hydroxide aqueous solution was added. The mixed solution was placed in a 40°C environment and stirred thoroughly. After stirring evenly, the temperature was raised to 80°C and stirred for an additional 2 h. Then, orthosilicate (TEOS) (5.0 mL 21.9 mmol) was added dropwise at a rate of 1 mL / min. Stirring continued until a large amount of white material was seen. After washing with methanol, it was placed in a vacuum drying oven at 100°C and dried for 12 h. The obtained material was named A1. Subsequently, 1.0 g of A1 was weighed and dispersed in 80 mL of toluene, and then 5 mL of 3-aminopropyltriethoxysilane was added. After mixing evenly, it was heated in N 2 Reflux overnight under atmosphere, filter, wash alternately with toluene and methanol, and then put the solid into a vacuum drying oven at 25°C to dry to obtain solid A2. Weigh 1.0g of the synthesized solid A2 and add a mixed solution of 100mL methanol and 0.75mL concentrated hydrochloric acid, stir at 50°C for 6h, filter and vacuum dry at room temperature for 12h to obtain solid A3, i.e. nano-mesoporous silicon material. Weigh 10mg of A3 powder in 1mL of water and ultrasonically disperse for 1.5h to obtain a well-dispersed mesoporous silicon solution (concentration: 10mg / mL).

[0041] (2) Preparation of nano-mesoporous silica@methylene blue composites

[0042] 100 μL of 1.0 mM methylene blue solution (MB) was added to the above mesoporous silica solution and incubated under stirring for 12 h. After standing for 30 min, the obtained suspension was centrifuged (5 min, 5000 rpm), then washed three times with PBS (10 mM, pH 7.0), and finally the obtained precipitate was dissolved in 1.0 mL PBS (10 mM, pH 7.0).

[0043] (3) Preparation of heavy metal ion aptamer-coated nano-mesoporous silica@methylene blue composites

[0044] The nano-mesoporous silica@methylene blue composite material obtained in step (2) was dispersed into 1.0 mL (10 mM, pH 7.0) solution containing 10 μM heavy metal ion aptamer, mixed and placed at 4°C for 6 h, the mixed solution was centrifuged (5 min, 5000 rpm), and washed with PBS three times. Then, the obtained coating material was dispersed in 1.0 mL PBS (10 mM, pH 7.0).

[0045] (4) Construction of electrochemical substrates for carrying small-volume samples

[0046] Use a diamond knife to separate the purchased ITO whole electrode into a 1cm×1cm matrix, and then glue the divided PCR tube sleeve into the ITO matrix with glue, and a simple ITO electrochemical cell is prepared. Subsequently, the ITO surface is cleaned several times with acetone, anhydrous ethanol, and distilled water to remove impurities on the electrode surface, and the electrode is dried with nitrogen. Then, the electrode is immersed in 1.0mol / L HCl for 10 minutes, and then the electrode surface is washed with distilled water. The cleaned electrode is immersed in 1:1:5 (v / v / v) HCl. 2 O 2 / NH 3 ·H 2 O / H 2 O mixed solution for 1 h to obtain ITO with -OH on the surface. Then, the electrode surface was cleaned with double distilled water and N 2 Dry the electrode.

[0047] (5) Research on universal heavy metal ion electrochemical sensors

[0048] In a 4°C environment, 500 μL of PBS (100 mM, pH 7.0) was placed in the ITO electrochemical cell of step (5), and 5 μL of different heavy metal ions were added and mixed. Subsequently, 45 μL of the composite material of step (3) was added, and the signal value of the released MB molecules was continuously collected by square wave voltammetry (SWV).

[0049] Based on the above steps (1)-(5), for 6 different heavy metal ions (such as Cd 2+ , Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + ), by changing the aptamer type in step (3) and keeping other steps unchanged, the detection of 6 different heavy metal ions can be achieved, verifying the universality of the prepared sensor.

[0050] like Figure 1As shown, when there is no DNA, the largest electrochemical signal is displayed due to the presence of a large amount of free MB; when there are no heavy metal ions, DNA completely seals the MB in the nano-mesoporous material, so the electrochemical signal is small or basically absent; when different heavy metal ions are present, a series of good electrochemical signals can be observed. No matter which heavy metal ions and their aptamers are selected to participate in the construction of the sensing strategy, they can cause the release of MB molecules in nano-mesoporous silicon, indicating that our sensing strategy has excellent universality and strong application value.

[0051] Example 2Cd 2+ Analysis and testing

[0052] Based on the above steps (1)-(5), select Cd 2+ As the research object, the aptamer used in step (3) is Cd 2+ The aptamer and other steps remain unchanged. The sensor was investigated in Cd 2+ Application in analytical testing. Figure 2 As shown, at 10 μM Cd 2+ In the presence of Cd, it has a good electrochemical signal. 2+ Under the condition of the presence of Cd, the electrochemical signal can be ignored, indicating that the sensor can achieve good results. 2+ Analytical testing.

[0053] Based on the above steps (1)-(5), select Cd 2+ As the research object, the aptamer used in step (3) is Cd 2+ By changing the Cd 2+ concentration (final concentration: 0, 0.01, 0.03, 0.05, 0.1, 0.5, 1, 3, 5, 8, 10, 20 and 30 μM), and other steps remained unchanged. Figure 3 As shown, with Cd 2+ As the concentration increases, the current intensity increases, and the sensor is sensitive to Cd 2 + The current response of the sensor is linearly related to the concentration. 2+ The linear correlation equation of concentration number is y=0.2874x+0.7603, R 2 =0.9923, the linear range is 0.01-10μM, and the detection limit is 0.0026μM (S / N=3), indicating that the sensor is sensitive to Cd 2+ Achieve high-sensitivity detection.

[0054] Example 3 Selectivity Experiment

[0055] like Figure 4As shown, based on the above steps (1)-(5), select Cd 2+ As the research object, the aptamer used in step (3) is Cd 2+ Aptamers, compared to other heavy metal ions, such as Cd 2+ , Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + , the sensor is only for Cd 2+ Has better response and better selectivity.

[0056] Example 4 Testing of Cadmium in Rice Samples

[0057] After the cadmium rice was ground, it was placed in a 1.0 mM hydrochloric acid solution overnight, filtered and centrifuged, and the diluted supernatant (10%) was taken for the experiment, and then the concentration addition experiment was used for testing. Figure 5 As shown, with different concentrations of Cd 2+ Added to the sample (final concentration: 0, 0.03, 0.1, 1 ~ and 5μM), the sensor involved in this patent application can well sense Cd 2+ This indicates that the sensor can be well applied to actual Cd 2+ Sample analysis.

[0058] Of course, the above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in the technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for constructing a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite material, characterized in that: The following steps are involved: (1) Preparation and functionalization of nano-mesoporous silica materials 0.5-1.0 g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 200-480 mL of double distilled water, and 1.0-3.5 mL of 1.0-2.0 mol / L sodium hydroxide aqueous solution was added. The resulting solution was placed in an environment of 20-40°C and stirred thoroughly. After stirring evenly, the temperature was raised to 60-80°C and stirred for an additional 1-2 h. Then, 2.0-5.0 mL of 10.0-21.9 mmol of orthosilicate TEOS was added dropwise at a rate of 0.5-1.0 mL / min. Stirring was continued until a large amount of white material was seen. After washing with methanol, the material was placed in a vacuum drying oven at 50-100°C and dried for 6-12 h. The obtained material was named A1. Subsequently, 0.5-1.0 g of A1 was weighed and dispersed in 60-80 mL of toluene, and then 1-5 mL of 3-aminopropyltriethoxysilane, mix well, reflux overnight under N2 atmosphere, filter, wash alternately with toluene and methanol, and then put the solid into a vacuum drying oven at 15-25°C to dry to obtain solid A2; weigh 0.5-1.0g of the synthesized solid A2, add 50-100mL of methanol and 0.5-0.75mL of concentrated hydrochloric acid mixed solution, stir at 37-50°C for 4-6h, filter and vacuum dry at room temperature for 10-12h to obtain solid A3, i.e. nano-mesoporous silicon material; weigh 5-10mg of A3 powder in 0.5-1.0mL of water, ultrasonically disperse for 1.0-1.5h to obtain a well-dispersed mesoporous silicon solution; (2) Preparation of nano-mesoporous silica@methylene blue composites 10-100 μL of 0.1-1 mM methylene blue solution MB was added to the mesoporous silica solution prepared in step (1), incubated under stirring for 6-12 h, allowed to stand for 10-30 min, and then the obtained suspension was centrifuged, then washed with PBS for 3 times, and finally the obtained precipitate was dissolved in 0.5-1.0 mL PBS; (3) Preparation of heavy metal ion aptamer-coated nano-mesoporous silica@methylene blue composites The nano-mesoporous silica@methylene blue composite material obtained in step (2) is dispersed in 0.5-1.0 mL PBS solution containing 5-10 μM heavy metal ion aptamer, mixed and placed at 1-4° C. for 3-6 hours, the mixed solution is centrifuged, and washed with PBS for 1-3 times; then, the obtained coating material is dispersed in 0.5-1.0 mL PBS; (4) Construction of electrochemical substrates for carrying small-volume samples The purchased ITO whole block electrode is divided into a (0.5-1) cm×(0.5-1) cm matrix with a diamond knife, and then the divided PCR tube sleeve is glued into the ITO matrix, and a simple ITO electrochemical cell is prepared; then, the ITO surface is cleaned several times with acetone, anhydrous ethanol, and distilled water in turn to remove impurities on the electrode surface, and the electrode is dried with nitrogen; then the electrode is immersed in 0.5-1.0 mol / L HCl for 5-10 min, and then the electrode surface is washed with distilled water; the cleaned electrode is immersed in a mixed solution of H2O2 / NH3·H2O / H2O with a volume ratio of (0.5-1):(0.5-1):(2-5) for 0.5-1h to obtain ITO with -OH on the surface, and then the electrode surface is cleaned with double distilled water, and the electrode is dried with N2; (5) Research on universal heavy metal ion electrochemical sensors In an environment of 4 to 12° C., 100 to 500 μL of PBS is placed in the ITO electrochemical cell of step (4), 1 to 5 μL of different heavy metal ions are added and mixed, and then 30 to 45 μL of the composite material of step (3) is added, and the signal value of the released MB molecules is continuously collected by square wave voltammetry (SWV); Wherein, the heavy metal ion is Cd 2+ , Hg 2+ , Pb 2+ , Cu 2+ , Ag + and Tl + ; The DNA chain of the heavy metal ion aptamer is as follows:

2. The method according to claim 1, characterized in that: The square wave voltammetry method SWV sets the potential range to -0.35 to -0.1 V and the amplitude to 0.025 V.

3. The method according to claim 1, characterized in that: The heavy metal ion is Cd 2+ .

4. The method according to claim 3, characterized in that The aptamer used in step (3) is Cd 2+ The aptamer is obtained by changing the Cd 2+ concentration, making Cd 2+ The final concentrations were: 0, 0.01, 0.03, 0.05, 0.1, 0.5, 1, 3, 5, 8, 10, 20 and 30 μM; 2+ As the concentration increases, the current intensity increases, and the sensor is sensitive to Cd 2+ The current response of the sensor is linearly related to the concentration. 2+ The linear correlation equation of concentration number is y=0.2874x+0.7603, R 2 =0.9923, the linear range is 0.01~10μM, and the detection limit is 0.0026μM.

5. The use of a universal heavy metal ion electrochemical sensor based on nano-mesoporous silicon composite material obtained by the construction method according to claim 1, characterized in that: Applied to the detection of cadmium content in cadmium rice.

Citation Information

Patent Citations

  • Construction of SiO2 carrier based release type electrochemical aptamersensor for sensitive detection of Hg<2+>

    CN110455897A